Relationship between frailty and depressive symptoms in older adults: role of activities of daily living and sleep duration - Song, Wei; Liu, Manyu; Ye, Ting; Wang, Dong; Yuan, Quan; Li, Fen; Wang, Qiushi; Ma, Yana (Frontiers in Medicine, 2024)
Introduction Previous studies have demonstrated that frailty is associated with depressive symptoms among older people and significantly increase the risk of difficulty in activities of daily living (ADL). However, uncertainties remain regarding the mechanisms behind such relationship. The aim of this study was to investigate the mediating effect of ADL in the relationship between frailty and depressive symptoms among older adults in China, and to explore to what extend sleep duration moderated the association between ADL and depressive symptoms. Methods In this study, we carried out cross-sectional descriptive analysis and 1,429 participants were included in the analysis. A survey was conducted using questionnaires and instruments measuring frailty, depressive symptoms, ADL and sleep duration. Bootstrap analyses served to explore the impact of ADL in mediating frailty and depressed symptoms, as well as the effect of sleep duration in moderating ADL and depressive symptoms. Results Compared to the robust group, the mediating effects of ADL between frailty and depressive symptoms were significant in the prefrail group and the frail group. The interaction term between sleep duration and ADL was significantly presented in the regression on depressive symptoms. Specifically, the Johnson–Neyman technique determined a range from 8.31 to 10.19 h for sleep duration, within which the detrimental effect of frailty on depressive symptoms was offset. Conclusion Sleep duration moderated the indirect effect of ADL on the association between frailty and depressive symptoms. This provides support for unraveling the underlying mechanism of the association between frailty and depressive symptoms. Encouraging older adults to enhance ADL and obtain appropriate sleep duration might improve depressive symptoms for older adults with frailty and prefrailty.